On The Convergence of Stability Domain on Time Scales - Nguyen, Thu Ha (H. : ĐHQGHN, 2017)
This paper studies convergence of the stability domains for a sequence of time scales. It is proved that if the sequence of time scales (Tn) converges to a time scale T in Hausdorff topology then their stability domains UTn will converge to the stability domain UT of T.